Perubahan Sosial Budaya dan Konflik pada Masyarakat Pesisir dan Pulau-Pulau Kecil di Indonesia - Rilus A Kinseng (Sodality: Jurnal Sosiologi Pedesaan, 2021)
Social change and conflict are an integral part of any society, including coastal and small island communities in Indonesia. Therefore, doing research on social change and conflict in these communities is very important. As a tribute to the late Prof. Tjondronegoro, this study analyzes briefly the role of Prof. Tjondronegoro in the study of social change in rural Indonesia. This study also analyzes socio-cultural changes, especially identity and sources of the changes, and social conflict in the coastal and small island communities. This is a qualitative study, conducted by examining relevant literatures. The study shows that the late Prof. Tjondronegoro was a lecturer on social change at graduate programme of IPB who had conducted researches regarding social change. Furthermore, the study indicates that socio-cultural changes have taken place in the coastal and small island communities due to changes of fishing technology, value system, tourism, mining activities, and government policies. Meanwhile, social conflicts have also taken place, mainly those related to access to livelihood sources. Thus, it can be concluded that the late Prof. Tjondronegoro played an important role in the development of research on socio-cultural change in rural Indonesia. Moreover, the coastal and small island communities in Indonesia have undergone social changes and conflict.